Análise dos limites ético-jurídicos da influência da religião evangélica no processo politico-eleitoral brasileiro - Santos, Valmir Nascimento Milomem (2015)
In recent decades, in each new election campaign, be they by majority or proportional, the faithful of the Evangelical churches have become key elements in the election disputes, due to the continuous decline in the number of Catholics and the correlated diffusion of Evangelical churches, namely the Pentecostal and Neo-Pentecostal churches. This study analyzes the participation of the Evangelical religion in the Brazilian electoral process, especially in the presidential elections of 2010 and 2014, so as to discover what the ethical-legal limits of the influence of this religious dimension in the Brazilian electoral process are. The ethical limits were evaluated based on the Protestant ethics, and the legal limits based on the Brazilian electoral legislation, discussing about the possibility of the participation of the Evangelical religion in the electoral campaigns being a mechanism of exercising power and/or persuasion with the pillar being religious moral values.